Study of Nano Silver Composite Sheet Derived From Pineapple Leaves for Hydrogen Sulphide Detection in Food Packing (International Journal of Food and Nutritional Sciences, 2022)
With an included H2S detection sensor, this research investigates the possibility of recycling pineapple leaf waste for food packaging packages. A regenerated cellulose sheet containing silver nanoparticles (AgNPs) was produced using microcrystalline cellulose (MCC) that was isolated from pineapple leaves. In comparison to natural cellulose, the ensuing nano-silver composite sheet had advanced shape and attributes, which include homogeneous AgNP distribution, extended floor area, and higher electrical conductivity. The composite sheet's colour changed incredibly from yellow to brown when exposed to H2S gas. As H2S awareness extended, this shade shift became more apparent, making it possible to quantify it and perhaps become aware of H2S in food packaging. The sensor proved touchy; it can come across H2S at as low as 0.1 ppm, which made it appropriate for early meal spoilage detection. Even though the primary findings are encouraging, similarly, research is needed to address troubles like selectivity closer to possible interfering gases and long-term stability. By resolving those issues and improving sensor performance, a sensible and low-cost solution for meal packaging programs may be evolved, improving meal protection and cutting down on waste.